2023
DOI: 10.3390/foods12183354
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of Selected Sourdough Saccharomyces cerevisiae Strains for the Production of a Craft Raspberry Fruit Beer

Viola Galli,
Manuel Venturi,
Simona Guerrini
et al.

Abstract: Recent interest in the special beer category has encouraged the search for novel brewing materials, including new ingredients and novel yeast strains, in order to differentiate the finished products. The aim of this work was to select non-brewing S. cerevisiae strains for the production of a fruit beer with raspberry. The in vitro tests and the wort fermentations allowed the selection of two sourdough S. cerevisiae strains, showing high maltose and maltotriose consumption, high ethanol production, and high via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Indeed, several studies have reported that S. cerevisiae baker's yeast strains can be employed to ferment brewer's wort [7,[14][15][16][17] and are typically used to brew common Eastern European beers like kvass [18] and Finland's sahti [19,20]. Sourdough cultures are also interesting reservoirs of maltose-negative yeasts for low-alcohol beer brewing [21], fruit beers [22] and craft beers with potential healthy added value [23][24][25][26]. Beers obtained using sourdough strains are also characterized by aromatic differences that are in consonance with their specific metabolic features, which appear to promote the synthesis of volatile compounds [14], in particular esters [1], instead of the fuse alcohols more abundant in brewing yeasts [27].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies have reported that S. cerevisiae baker's yeast strains can be employed to ferment brewer's wort [7,[14][15][16][17] and are typically used to brew common Eastern European beers like kvass [18] and Finland's sahti [19,20]. Sourdough cultures are also interesting reservoirs of maltose-negative yeasts for low-alcohol beer brewing [21], fruit beers [22] and craft beers with potential healthy added value [23][24][25][26]. Beers obtained using sourdough strains are also characterized by aromatic differences that are in consonance with their specific metabolic features, which appear to promote the synthesis of volatile compounds [14], in particular esters [1], instead of the fuse alcohols more abundant in brewing yeasts [27].…”
Section: Introductionmentioning
confidence: 99%